Birth Rates and Cesarean Indications at Selçuk University During Five -Year Period - Osman Balcı; Suna Özdemir; Alaa Mahmoud; Ali Acar (Medical Network, 2010)
OBJECTIVE: The aim of the study is to evaluate the rates, indications and complications of cesarean sections (CS) in our hospital during 5 years. STUDY DESIGN: Patients who gave birth between January 2004 and December 2008 in our clinic were enrolled in this study and retrospectively analyzed. The CS rates, its complications, indications, and maternal mortality and morbidity rates were studied. RESULTS: The total number of births in five years was 11121. Of these births, 4818 (43.32%) were vaginal births and the remaining 6303 (56.67%) were cesarean deliveries. Previous cesarean deliveries were the major indication with 2118 (33.6%) cases, fetal distress with 880 (13.96%) cases, elective cesarean with 715 (11.34%) and cephalo-pelvic disproportion (CPD) with 622 (9.86%) cases. Eight cases of maternal mortality were detected in CS group (12.69/10000). The morbidity rate was found to be 12%. CONCLUSIONS: The rates of cesarean deliveries are increasing day by day. The increased rates of previous cesarean deliveries are a critical factor for the risks of recurrent surgeries and cost-effectiveness. We concluded that to determine the real indications for primary cesarean deliveries and to be more selective and careful are assumed to decrease the cesarean delivery rates.